Nepal Development Update, May 2016 : Remittances at Risk - World Bank (World Bank, Kathmandu, 2016)
During 2015, and in the span of six-months, Nepal was hit by two major shocks. The first one was the April 2015 earthquakes that caused a huge loss of life and assets. The second shock has come in the form of a near complete disruption of external trade following the adoption of the new Constitution. Reflecting both the earthquake and trade related disruptions, inflation spiked to over 12 percent (y/ y) by mid-January rising 5 percentage points in just four months from mid-September 2015. This was the highest inflation level since FY2009, with increases in food and non-food prices contributing equally to the spike. As the trade disruptions ended, inflation has eased to back to single digits.